MICROELECTRONICS and NANOTECHNOLOGY (MN)

Question 1: Semiconductor Fundamentals

August 2009

## Questions

All questions are in this link

# Solutions of all questions

1)

$E = Ak^\alpha ; k=\sqrt{k_x^2+k_y^2}$

\begin{align*} D(E)&=\frac{\pi(k+\triangle k)^2 - \pi k^2}{\frac{2\pi}{W}\cdot\frac{2\pi}{L}}\cdot\frac{1}{\triangle E}\cdot\frac{1}{A}\\ &\approx \frac{\cancel{WL}}{4\pi^2}\cdot(\pi\cdot2k\triangle k)\cdot\frac{1}{\triangle E}\cdot\frac{1}{\cancel{A}}\\ &=\frac{1}{2\pi}k\frac{\triangle k}{\triangle E}\approx \frac{1}{2\pi}k\frac{dk}{dE} \end{align*}

Now; $k = \bigg(\frac{E}{A}\bigg)^\frac{1}{\alpha}$\\

\begin{align*} \frac{dk}{dE}&=\frac{1}{\alpha}\cdot\frac{E^{\frac{1}{\alpha}-1}}{A^{\frac{1}{\alpha}-1}}\cdot\frac{1}{A}\\ \therefore D(E)&=\frac{1}{2\pi}\cdot\frac{E^{\frac{1}{\alpha}}}{A^{\frac{1}{\alpha}}}\cdot\frac{1}{\alpha}\cdot\frac{E^{\frac{1}{\alpha}-1}}{A^{\frac{1}{\alpha}-1}}\cdot\frac{1}{A}\\ &=\frac{1}{2\pi\alpha}\cdot\frac{E^{\frac{2}{\alpha}-1}}{A^{\frac{2}{\alpha}-1+1}}\\ &=\frac{A^{\frac{-2}{\alpha}}}{2\pi \alpha}E^{\frac{2}{\alpha}-1} \end{align*}

--------------------------------------------------------------------------------------

2)

At $T=0; f(E)=1$ upto $E=E_F$


\begin{align*} \therefore n(E) &=\int_{E_C}^{E_F}D(E)dE\\ &=\int_{E_C}^{E_F}\frac{A^{\frac{-2}{\alpha}}}{2\pi \alpha}\cdot E^{\frac{2}{\alpha}-1}dE\\ &=\frac{A^{\frac{-2}{\alpha}}}{2\pi \alpha}\frac{E^{\frac{2}{\alpha}}}{2/\alpha}\bigg\vert_{E_C}^{E_F}\\ &= \frac{A^{\frac{-2}{\alpha}}}{4\pi}\cdot\bigg(E_F^{\frac{2}{\alpha}}-E_C^{\frac{2}{\alpha}}\bigg). \end{align*}

If we take $E_C$ as the reference energy i.e. $E_C = 0$ then;

$n(E) = \frac{A^{\frac{-2}{\alpha}}}{4\pi}E_F^{\frac{2}{\alpha}}.$

 --------------------------------------------------------------------------------------


3)

Boltzmann statistics; $f(E)\approx e^{-(E-E_F)/kT}$

$\therefore n(E) = \int_{E_C}^{\infty}D(E)f(E)dE$

taking $E_C$ as reference; i.e. $E_C = 0$

\begin{align*} n(E) &= \int_0^\infty\frac{A^{\frac{-2}{\alpha}}}{2\pi\alpha}e^{-(E-E_F)/kT}\cdot dE\cdot E^{\frac{2}{\alpha}-1}\\ &=\frac{A^{\frac{-2}{\alpha}}}{2\pi\alpha}\cdot e^{E_F/kT}\int_0^\infty e^{-E/kT}\cdot E^{\frac{2}{\alpha}-1}dE \end{align*}

Let;

$\frac{E}{kT} = t \:\:\:\:\:\:\:\:\:\:\therefore dE = kTdt$

\begin{align*} \therefore n(E)&= \frac{A^{\frac{-2}{\alpha}}\cdot e^{E_F/kT}}{2\pi\alpha}kT\int_0^\infty e^{-t}\cdot (tkT)^{\frac{2}{\alpha}-1}dt\\ &= \frac{A^{\frac{-2}{\alpha}}\cdot e^{E_F/kT}}{2\pi\alpha}\cdot(kT)\cdot(kt)^{\frac{2}{\alpha}-1}\int_0^\infty e^{-t}\cdot t^{\frac{2}{\alpha}-1}dt\\ \end{align*}

Now; $\Gamma (z) = \int_0^\infty dt e^{-t}t^{z-1}$

$\therefore n(E)= \frac{A^{\frac{-2}{\alpha}}e^{E_F/kT}}{2\pi\alpha}(kT)^\frac{2}{\alpha}\cdot\Gamma(2/\alpha)$

--------------------------------------------------------------------------------------

d)

$v_{avg} = \mu E \text{ (So, we use the 2nd plot)}$



$\therefore \mu = \frac{v_{avg}}{E}$

So, we need to find avg. velocity and divide by the constant electric field value to find mobility.

$v_{avg} = \frac{V(0)+V(\tau_1)}{2} = \frac{V(\tau_1)}{2} = \frac{qE_x\tau_1}{2m^*}$



$\therefore \mu = \frac{qE_x\tau_1}{2m^*E_x} = \frac{q\tau_1}{2m^*}.$

 --------------------------------------------------------------------------------------
e)

For elastic scattering, velocity cannot change. As the velocity goes to zero here, it cannot be elastic.
Ans: ii



## Alumni Liaison

Basic linear algebra uncovers and clarifies very important geometry and algebra.

Dr. Paul Garrett